Numerical analysis of a fully developed non-isothermal particle-laden turbulent channel flow - Jaszczur, M. (Archives of Mechanics, 2011)
Turbulent non-isothermal fully-developed channel flow laden with small particles was investigated through Direct Numerical Simulation (DNS), combined with tracking of the individual particles. The simulations are performed at Reτ=180 and 395, with Pr = 1.0. The Euler–Lagrange approach with point-particle modeling has neglected the influence of the particles on the fluid and inter-particle interactions. The focus is centered on the interactions between particles and turbulence and their effect on the concentration and temperature of the particles. DNS shows that the clustering and segregation of particles near the wall, due to turbophoresis, is strongly related to the quality of the velocity field and these phenomena cannot be reproduced with other types of simulation. The presented data were obtained using direct numerical simulation and show new effects related to heat exchange for the turbulent flow with small particles. It has been discovered that a large increase of concentrations of the particles close to the wall and in low-speed streaks, where temperatures differ from the mean temperature, strongly affect the mean temperature of the particles.